REPRESENTASI BUDAYA JAWA DI ERA MODERN PADA FILM LOSMEN BU BROTO - Putri, Tiara Nabila Nugraha; Bernard Realino Danu Kritstianto (LPPM Stikosa - AWS, 2025)
In modern dynamics, culture undergoes a significant transformation due to the influence of globalization and technology. Javanese culture as one of Indonesia's cultural heritage experiences challenges in maintaining identity in the midst of globalization. Film as a medium that has a wide and deep reach, has the potential to reflect culture and shape people's perceptions. The purpose of this study is for how Javanese culture is represented in contemporary artworks such as the film